Medical leadership training varies substantially between UK medical schools: Report of the leadership in undergraduate medical education national survey (LUMENS). (2nd January 2023) - Aldersley, Katherine; Gibb, Jonathan; Grainger, Charlotte; Abou-el-Ela-Bourquin, Bilal; Badhrinarayanan, Shreya; Bhanot, Ravina; Clark, Ryan; Douglas, Hannah; Fukui, Akiko; Hana, Zac; Imtiaz, Inshal; Kalsi, Tejinder; et al.
Abstract: Background: Doctors are increasingly expected to demonstrate medical leadership and management (MLM) skills. The Faculty of Medical Leadership and Management (FMLM) has published an indicative undergraduate curriculum to guide the development of MLM content at UK medical schools. Method: Students from 30 medical schools were surveyed to determine their understanding of MLM teaching at their school. Timetables for 21 schools were searched for MLM-related keywords. Student-reported teaching and timetabled teaching were coded according to predefined themes. Aggregated demographic and postgraduate performance data were obtained through collaboration with the Medical Student Investigators Collaborative (msico.org). Results: Whilst 88% of medical students see MLM teaching as relevant, only 18% believe it is well integrated into their curriculum. MLM content represented ∼2% of timetabled teaching in each 5-year undergraduate medical course. Most of this teaching was dedicated to teamwork, performance/reflection and communication skills. There was minimal association between how much of a topic students believed they were taught, and how much they were actually taught. We found no association between the volume of MLM teaching and performance in postgraduate examinations, trainee career destinations or fitness to practice referrals. Conclusion: Our findings demonstrate limited and variable teaching of MLM content. Delivery was independent of broader teaching and assessment factors.